Shifting from the old frame of reference to (w)holistic teacher-student relationship in higher education institution: A case of the University of The Free State - Okoye, F. (South African Journal of Higher Education, 2023)
This quantitative study examines the student’s perception of what their relationship with their lecturers should be to enhance higher education teaching and learning, as well as students’ success. The finding of the study reveals the students’ perception and expectations of a lecturer’s role in maintaining good pedagogical relations at the higher-education level. These roles were framed within four cardinal themes: students’ academic development, social relationships, respect and trust, and the ethics of care. The finding also reveals that the students hold substantial expectations of the lecturers to take a lead in driving social relationship. The student does not only expect the lecturer to pay attention to his or her academic progress, moral and personal development but also to care, respect, trust and even the student’s non-academic activities and goals are considered to be the lecturer’s prerogative. The study recommends institutional strategies for promoting effective teaching and learning through relational pedagogy drive, reduction of large-size classes, raising student voice and well-being, and establishing ethics of care or caring culture as an integral part of the Institution’s teaching philosophy. The study argues that the mainstream pedagogical relationship serves as a constructive way of understanding decolonialism in Africa, as well as an antidote to the persevering colonial infrastructures found in higher education.